Trends in pharmacological emergency treatment of patients suffering from schizophrenia over a 16-year observation period. (July 2018) - Edlinger, Monika; Welte, Anna-Sophia; Yalcin-Siedentopf, Nursen; Kemmler, Georg; Neymeyer, Felix; Fleischhacker, W. Wolfgang; Hofer, Alex
Abstract : Patients suffering from schizophrenia are often treated in locked psychiatric units because of psychomotor agitation, hostility and aggressive behavior, or suicidality. Because of legal conditions, investigations on these acutely ill patients are difficult, and many studies do not represent 'real-life psychiatry'. This retrospective survey was conducted at the Department of Psychiatry, Psychotherapy and Psychosomatics of the Medical University, Innsbruck, Austria. Data were collected from the records of all adult inpatients suffering from a schizophrenia spectrum disorder according to the International Classification of Diseases, 10th ed. (ICD-10) (F2x) who had been admitted to a locked unit in 1997, 2002, 2007, and 2012. In addition to demographic data, diagnoses at the time of admission, length of stay at the locked unit, and psychopharmacological treatment (3 h before and following admission) were recorded. The mean length of stay at a locked unit decreased significantly from 11.8±4.43 days (mean±SD) in 1997 to 8.5±12.96 days (mean±SD) in 2012. The use of antipsychotics decreased nonsignificantly from 1997 to 2012. Despite an increasing use of second compared with first-generation antipsychotic drugs over the course of time, haloperidol was the most frequently used single compound in all investigated years except 2012. The majority of medications were administered orally. The use of benzodiazepines did not change substantially over the course of time. All in all, pharmacological emergency treatment of patients suffering from schizophrenia spectrum disorders in locked units was in line with current treatment guidelines, which recommend the use of second-generation antipsychotic drugs, monotherapy, oral application, and cautious dosing. Abstract : Supplemental Digital Content is available in the text.